Metode Penanaman Pendidikan Islam pada Anak Menurut Abdullah Nashih Ulwan - Nur Khosiin (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2021)
Abdullah Nasih Ulwan’s provides several points of view in the realm of methods of planting Islamic education in children which can later be used as a means to achieve the goals of Islamic education. This research uses the documentation method with a descriptive-interpretative approach, namely an attempt to describe the interpretation of some of the texts of the book at-tarbiyah al-aulad fi al-Islam in the third chapter. As for the primary data source is the book at-tarbiyah al-aulad fi al-Islam, the secondary data source is books and related literature, while the data analysis used descriptive analysis. The results of this study there are five methods of planting Islamic education for children, namely educating by example, customary habits, advice, supervision, and through punishment.